Linguistic Adaptation and Psychometric Properties of the University Student Depression Inventory (USDI) - Κουτσουμπής Αντώνης; Καριπίδου Ευγενία; Μπουρελάκη Σοφία; Τσαρτσίδου Αγγελική; Τσαούσης Ιωάννης (Psychology: the Journal of the Hellenic Psychological Society, 2018)
The present study provides an adaptation of the University Student Depression Inventory (USDI) in Greek language, and assesses its psychometric properties. After its translation and conceptual adaptation, the Greek version of the USDI was administered to 248 students of the University of Crete. Confirmatory Factor Analysis was used to evaluate its factorial design, comparing four different factorial models: the one factor model, the three factors model, the hierarchical model, and the bifactor model. Statistical analyses showed that the bifactor model had the best adaptation in Greek population, after the removal of an item (item seven). To assess the validity of the scale, four additional measures of related constructs (i.e., personality, well-being, depression, and anxiety) were administered. Those measures were used to establish the concurrent, convergent and divergent validity. Omega index was used to test the internal consistency of the scale. Overall, results showed that the Greek version of the USDI is a valid and reliable tool for measuring depression in Greek students.